An investigation on ESL undergraduates' attitudes towards learning English literature across learning styles / Khairunnisa Azmar - Azmar, Khairunnisa (2013)
The study of literature has gained its momentum in English language teaching. However, literature is regarded as a burden and difficult to learn by the students. Besides that, how the students learn is another aspect that should be considered in learning English literature. This is because students learn differently between one another. Thus, their attitudes towards literature might be influenced by their preferred learning styles. Therefore, this study was conducted to investigate the ESL undergraduates’ attitudes towards learning English literature across learning styles. Quantitative research design was chosen and 200 respondents were chosen randomly to participate in this study. The results showed that the respondents have positive attitude towards learning English literature and their preferred learning styles are active, sensing, visual and sequential. However, there is no statistically significant difference between the attitudes of the respondents and the different learning styles.